Kegiatan Alih Media Koleksi Antiquariat Di Pusat Perpustakaan Dan Penyebaran Teknologi Pertanian - Safanawati, Siti Kartika; CMS, Samson (Program Studi Ilmu Perpustakaan dan Informasi, Universitas Islam Nusantara, 2020)
The Center for Library and Distribution of Agricultural Technology is one of the special libraries that manages rare library materials, namely antiquariat library materials. Antiquariat library material is a rare library from the Dutch colonial era which contains information about agriculture. Antiquariat library materials require special handling to preserve existing information, this conservation process is called the Preservation process. Preservation is a way to preserve library materials which is not only physical preservation but also includes preservation of information contained therein. Preservation is an effort so that the information contained therein can still be accessed and prevented from extinction. This study uses a qualitative approach, with more emphasis on the way of description in expressing the phenomena experienced by research subjects. As for the subjects of the study are the Library and Agricultural Technology Dissemination of Bogor City. The object under study is the preservation process carried out by the Central Library and Distribution of Agricultural Technology in preserving antiquariat library materials. The results of this study indicate that the preservation process carried out by the Central Library and Distribution of Agricultural Technology has been going well. The process of observation carried out by the Central Library and Distribution of Agricultural Technology is to carry out the process of media transfer by digitizing using two methods, namely scanning and capturing. The results of the digitization are presented in the form of e-books and CD-Roon that can be accessed by users only at the Agricultural Library and Technology Center.